Development of Brain-Based Learning Worksheets for One-Variable Linear Equations in Grade VII of a Private Junior High School in Bandung - Nurul Fatma Dewi Mardianto (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to develop a Brain-Based Learning-based LKPD on Single Variable Linear Equations for seventh-grade students at a private junior high school in Bandung. The method used is the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of validation by subject matter, media, and language experts showed that the LKPD developed was highly valid with an average score of 85.2%. The practicality test conducted by teachers and students yielded an average score of 83.47%, which falls into the highly practical category. Meanwhile, the effectiveness of the LKPD was measured through pretest and posttest tests, which showed an increase in learning outcomes with an average score rising from 56.52 to 80.09, as well as an N-gain score of 0.5855, which is classified as moderate. The classical mastery level also increased to 80.95%. Therefore, the Brain Based Learning-based LKPD is declared valid, practical, and effective in supporting the mathematics learning process and is able to improve students' conceptual understanding and learning activity. The results of this study are expected to be an alternative innovative teaching material that supports more contextual learning and is in line with how the brain works.